Digital Transformation Through Servant Leadership Model: A Qualitative Analysis - Sini PILLAI; Vishnu SURESH (Communications of International Proceedings, 2022)
The impact of the fourth Industrial revolution has redefined the future of work aspects. Businesses have adopted holistic strategies to evolve on the front line defining the processes that address quality, work-life balance, and consistency in workforce performance. When organizations around the whole world were operating amidst the pandemic, a remotely distributed workforce have become the new normal. But creating a high-performance team with a remotely distributed workforce, especially in a gig economy seems challenging and the work terrain calls for a changed transformational leadership model, the servant-based model. The paper attempts to develop a realistic servant leadership model for managing a remotely distributed workforce by applying Multi-Layer Analysis(MLA). A standard questionnaire measuring various dimensions of servant leadership is administered among knowledge managers managing the remotely distributed workforce. The success factors of a remotely distributed workforce are mapped with the 4E framework of Servant Leadership. Employee competence and organizational quality were identified as the major influencing outcomes of servant leadership. The recommended servant leadership model will enable drift towards a digital transition among remotely working employees from a managerial perspective.
Keywords: Digital business transformations; Servant leadership; Remote distributed workforce; 4E Model.